Fear Not, for I Am with You Again (Socially Distanced): A Qualitative Thematic Analysis of Megachurch Post-covid Lockdown Re-opening Videos on Facebook - Wold, Todd L. (Journal of religion, media and digital culture, 2022)
Churches in the United States closed their doors to in-person gatherings during the covid-19 lockdown in March of 2020. As conditions improved, churches began re-opening to indoor worship services, instituting safety measures to comply with cdc guidelines. Churches used social media to promote their re-opening to their congregations. With the goal of evaluating the video messages of churches promoting their re-opening, the study analyzes the content of Facebook videos from non-denominational megachurches between June and October 2020. This qualitative thematic analysis explores how the videos address the threat of covid-19, the risk of attending in-person services, and the efficacy of health and safety measures. The inductive analysis was sensitized by the extended parallel processing model, ritual communication theory, and the concept of security theater. The themes identified have potential implications for future religious and health communication research, especially concerning contentious safety protocols, managing fear and anxiety, liability concerns, livestreaming technology, and more digitally transient congregations.